2013
DOI: 10.1080/02673843.2013.806270
|View full text |Cite
|
Sign up to set email alerts
|

Social withdrawal in Russian youth: using the Extended Class Play to examine socio-emotional and academic adjustment

Abstract: This study explored the socio-emotional characteristics and school adjustment of shy/socially withdrawn youth and examined the properties of the Extended Class Play (ECP), a common peer measure of shyness/withdrawal and other social behaviour with Russian early adolescents (n ¼ 106; mean age 12.5). Associations between the ECP scores and teacher-and self-reports of adjustment (e.g. internalising problems) provided evidence supporting use of the ECP with Russian adolescents. Similar to North American studies, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Recent studies, indeed, have highlighted that when extremely anxious, students show more reluctant and rejecting behavior toward school and instructions than their less anxious peers (e.g., [77]). Besides this, students with severe anxiety tend to avert interaction and exhibit low social and emotional competences (e.g., [78,79]). Effectively, students with high anxiety levels prefer avoidant rather than support seeking strategies (i.e., teacher support) [80,81].…”
Section: The Moderating Role Of Academic Anxietymentioning
confidence: 99%
“…Recent studies, indeed, have highlighted that when extremely anxious, students show more reluctant and rejecting behavior toward school and instructions than their less anxious peers (e.g., [77]). Besides this, students with severe anxiety tend to avert interaction and exhibit low social and emotional competences (e.g., [78,79]). Effectively, students with high anxiety levels prefer avoidant rather than support seeking strategies (i.e., teacher support) [80,81].…”
Section: The Moderating Role Of Academic Anxietymentioning
confidence: 99%
“…These studies show that shy children are prone to internalizing difficulties (e.g., loneliness and depressive symptoms) as well as peer problems (e.g., peer rejection), similar to the findings from more recent research on Chinese and Western samples. These findings might be partly due to the stronger emphasis on children's academic achievement over the development of self-expression in non-Western schools (e.g., Chen et al, 2003;Kalutskaya & Buhs, 2013). Specifically, although some studies in China reported a significant negative association between shyness and children's academic performance (Liu et al, , 2015, the majority did not find such a link (China: Chen, Chang, & He, 2003;Chen et al, 2013;Russia: Kalutskaya & Buhs, 2013;India: Prakash & Coplan, 2007).…”
Section: Empirical Evidence From Non-western Culturesmentioning
confidence: 99%
“…In addition to China, researchers have begun to explore the social and psychological difficulties associated with shyness in other non‐Western societies, including India (Bowker & Raja, ; Prakash & Coplan, ), Japan (Okada, Tani, Ohnishi, Nakajima, & Tsujii, ), and Russia (Kalutskaya & Buhs, ). These studies show that shy children are prone to internalizing difficulties (e.g., loneliness and depressive symptoms) as well as peer problems (e.g., peer rejection), similar to the findings from more recent research on Chinese and Western samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not getting along signals problems in peer relations, and if one keeps from getting involved with/close to others, it might signal withdrawal or asocial behaviour. In both cases, one might not be as well connected and it might lead to non-belonging from the peer group, which in turn, can be linked with poor school adjustment (Kalutskaya & Buhs, 2013), school dislike. We included variable Hanging around with kids who get into trouble in the study, as indicative of deviant peer association (see Snyder et al, 2005).…”
Section: Independent Variablesmentioning
confidence: 99%